ANATOMY OF THE ANTERIOR PART OF THE ADULT MANDIBLE - A. K. IORDANISHVILI; M. I. MUZYKIN; A. E. NAGAIKO; E. S. VERBITSKY (Кубанский научный медицинский вестник)
Aim. Anatomic variations of a structure of the anterior part of the mandible with account of gender for the characteristic of the internal structure of bone tissue and specification of the topographical features of the inferior dental canal for obtainment of osteal material for an autoplasty of an alveolar process (part) of jaws are presented in the article.Material and methods. In the course of a clinical-anatomic research performed at 600 men and 600 women aged from 18 up to 55 years the specific anatomic features of a structure of the mandibular mental region were studied. 20 non-identified skulls (10 male and 10 female) with mandibles at the background of partial loss of teeth with various types of the mental region and the mandible sections at the level of apexes of the canine and the central incisors roots for comparative evaluation of morphometric research data and visual identification of the inferior dental canal on the anatomic material and 3D pictures were also studied. Results. Studying of the specific anatomic features of a structure of the mental region of the mandible allowed to allocate 5 types of an anatomic structure of the mental region (spherical or spheroid; oval or ellipsoidal; wedge-shaped or "acute"; rectangular; flat) taking into account gender differences. The internal structure of the bone tissue of the mental region and the specific features of the inferior dental nerve endings location after a foramen were evaluated.Conclusion. The highest amount of compact substance was observed in the wedge-shaped and rectangular types of the mandibular mental region.